1998
DOI: 10.1002/(sici)1520-6343(1998)4:1<1::aid-bspy1>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide binding and active site structure in heme-copper oxidases: Normal coordinate analysis of iron-cyanide vibrations of CN− complexes of cytochromesba3 andaa3

Abstract: The cyanide isotope‐sensitive low‐frequency vibrations of ferrous cyano complexes of cytochrome a3 are studied for cytochrome ba3 from Thermus thermophilus and cytochrome aa3 from bovine heart. Cyanide complexes of ba3 display three isotope sensitive frequencies at 512, 485, and 473 cm−1. The first is primarily an Fe—C stretching motion, whereas the lower wavenumber modes are bending motions. These iron‐cyanide vibrations are independent of the redox levels of the other metal centers in the protein. On the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 60 publications
2
38
0
Order By: Relevance
“…Four 14 N atoms, presumably donated by histidine residues of the protein, provide a strong equatorial ligand field about Cu B and a second CN – is coordinated through the carbon atom to Cu B in an axial position. Although the Fe–CN modes were detected by RR spectroscopy in all of the CN-adducts, the corresponding Cu B –CN modes were not observed. …”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Four 14 N atoms, presumably donated by histidine residues of the protein, provide a strong equatorial ligand field about Cu B and a second CN – is coordinated through the carbon atom to Cu B in an axial position. Although the Fe–CN modes were detected by RR spectroscopy in all of the CN-adducts, the corresponding Cu B –CN modes were not observed. …”
Section: Introductionmentioning
confidence: 89%
“…Structural information of the O 2 -binding binuclear center of ba 3 oxidase and in cytochrome c oxidase (C c O) superfamily have been determined from a great number of spectroscopic and computational studies of the CO–, CN – , and NO-bound adducts. In general, CO binds to the ferrous (Fe 2+ ) form of heme a 3 , whereas CN – and NO bind to both oxidized (Fe 3+ ) and reduced (Fe 2+ ) forms of heme a 3 . Because of the unusual ligand-binding kinetic properties of its binuclear center, cytochrome ba 3 from T. thermophilus is unique among the heme-copper oxidases in being susceptible to a detailed analysis of its ligation dynamics in the heme a 3 -Cu B site. Resonance Raman (RR), electron nuclear double resonance (ENDOR), and electron paramagnetic resonance (EPR) spectroscopies, in conjunction with the permutations of 13 C- and 15 N-labeled cyanide have indicated that the reaction of oxidized ba 3 with cyanide yields a heme a 3 (II)-CN·Cu B (II)–CN complex. It has been demonstrated that cytochrome ba 3 reacts slowly with excess HCN at pH 7.4 to create a form of the enzyme in which Cu A , heme b , and Cu B remain oxidized, while heme a 3 is reduced by one electron, presumably with the formation of cyanogen . The results supported a model in which one CN – binds through the carbon atom to ferrous heme a 3 , supporting a low-spin ( S = 0) configuration on the Fe; bridging by this cyanide to the Cu B is weak or absent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another intriguing feature of this CN-bound CcO structure is the significant bending of the Fe–C–N angle (96°). This bent structure is in line with previous resonance Raman characterizations and might be caused by the weak π-accepting ability of cyanide, which makes it easier to adopt a bent geometry compared to the isoelectronic Fe-CO complexes. …”
Section: Reactions Mediated By Heme–oxygen Intermediates Other Than C...mentioning
confidence: 99%
“…Amide-I vibrations involve primarily combinations of backbone carbonyl stretches. 26,27 The 'local' carbonyl stretches, corresponding to individual amino acids within the protein, form the basis for the delocalized normal modes. 28 The frequencies of the normal modes are given by the frequencies of the local C]O stretches as well as the magnitude of the couplings between these local oscillators.…”
Section: Motivationmentioning
confidence: 99%